Impacts of climate change on agro-ecological landscapes in the coastal area of the Thai Binh province (Vietnam) using the Delphi technique. Issue 2 (18th May 2015) - Trinh Hai, Le; An Thinh, Nguyen; Anh Tuan, Tran; Dinh Cham, Dao; The Anh, Luu; Luu Thu Thuy, Hoang; Manh Ha, Nguyen; Quoc Bao, Tran; Van Huong, Le; Dinh Khanh, Uong; Thi Mai, Bui; Phuc Tuan, Tong; et al.
Abstract : Purpose: – This paper aims to facilitate the joint assessment of issues related to the agricultural systems, i.e. agriculture, aquaculture and climate change (CC) response strategies, in the coastal districts with a panel of stakeholders; and to evaluate the level of agreement on the topics under consideration and potentially identify the most promising approaches to assessing CC affecting agricultural systems in the area and identify relevant and adequate response strategies. Design/methodology/approach: – Stakeholder Delphi technique – its assessment is an interactive method of qualitative research used to facilitate the interactive participation of varied and conceivably hierarchical and antagonistic stakeholder groups. Findings: – The most important result for the province is that the impact of climate change on agro-ecological landscapes (poverty and near river areas) is the duration of cold weather, more frequent and extreme. Moreover, Kendall's W test gave a score of 0.547, which indicates a "strong" stakeholder agreement and the "confidence in ranks" being "high" in Thai Binh (Vietnam). Originality/value: – The scientific results in this study are intended to serve as relevant knowledge-inputs and direct contributions to capacity-building for the local partners (stakeholders and local authorities). These local partners are engaged in policy-making and effective planning and implementation of climate response measures in the districts in the province of Thai Binh.